REDENOMINASI, NILAI MATA UANG DAN EKSISTENSI EMAS DI ERA COVID-19 - Chairul Ihsan Burhanuddin; Burhanuddin Burhanuddin (AkMen JURNAL ILMIAH, 2020)
It is difficult to understand the economic turmoil that has hit Indonesia, especially in various parts of the world. This is related to the outbreak of coronavirus or the familiar one called covid-19. The economic contraction is clearly striking in various sectors, ranging from trade, manufacturing, to capital markets. Another problem that is no less strange is the value of the rupiah which continues to slump sharply followed by the upheaval in the value of gold whose price continues to soar. Not to mention the issue of rupiah redenomination that continues to roll behind economic uncertainty. This research provides an economic perspective and essence that needs to be built on the various economic problems and issues facing the Country of Indonesia. Therefore, from various explanations of the point of view on the issues that are being discussed in this study provide input to the relevant parties in making decisions in addressing the problem. The importance of the results of this study is to provide information and analysis on how to make decisions and attitudes behind the economic problems that are facing today.